2007
DOI: 10.1124/dmd.107.016196
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition in Humans of Raltegravir (MK-0518), an Anti-AIDS Drug Targeting the Human Immunodeficiency Virus 1 Integrase Enzyme

Abstract: ABSTRACT:Raltegravir is a potent human immunodeficiency virus 1 (HIV-1) integrase strand transfer inhibitor that is being developed as a novel anti-AIDS drug. The absorption, metabolism, and excretion of raltegravir were studied in healthy volunteers after a single oral dose of 200 mg (200 Ci) of [ 14 C]raltegravir. Plasma, urine, and fecal samples were collected at specified intervals up to 240 h postdose, and the samples were analyzed for total radioactivity, parent compound, and metabolites. Radioactivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
225
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(237 citation statements)
references
References 13 publications
9
225
1
2
Order By: Relevance
“…This interaction with DTG is likely the combined effect of UGT and CYP3A4 induction. This is consistent with etravirine and efavirenz causing modest decreases (20-40%) in the pharmacokinetics of raltegravir, a sensitive UGT substrate (Kassahun et al, 2007;Iwamoto et al, 2008). Support for a role of CYP3A4 induction was demonstrated by coadministration of the potent CYP3A4 inhibitors lopinavir/ritonavir or darunavir/ritonavir that counteracted the decrease in DTG exposure by etravirine (Song et al, 2011c).…”
Section: Discussionsupporting
confidence: 58%
“…This interaction with DTG is likely the combined effect of UGT and CYP3A4 induction. This is consistent with etravirine and efavirenz causing modest decreases (20-40%) in the pharmacokinetics of raltegravir, a sensitive UGT substrate (Kassahun et al, 2007;Iwamoto et al, 2008). Support for a role of CYP3A4 induction was demonstrated by coadministration of the potent CYP3A4 inhibitors lopinavir/ritonavir or darunavir/ritonavir that counteracted the decrease in DTG exposure by etravirine (Song et al, 2011c).…”
Section: Discussionsupporting
confidence: 58%
“…The differences observed in HIV kinetics led us to examine the sensitivity of the above cell populations to antiretroviral drugs targeting the early stages in the viral life cycle. To address this, cells were treated with zidovudine (AZT) (10 M), efavirenz (EFV) (0.1 M) (4,23,33), or the integrase inhibitors 118-D-24 (80 M) (26) and raltegravir (50 nM), which was recently approved for clinical use (8)(9)(10), at various time points postinfection. The inhibition of viral replication was assessed by quantifying intracellular p24 Gag levels 48 h postinfection.…”
Section: Kinetics Of Hiv Infection In 24-and 48-h-stimulated Cd4mentioning
confidence: 99%
“…The major circulating entity in plasma was the parent compound (69% of the total drug-related material in plasma), whereas most of the drug-related material in urine was accounted for by the glucuronide derivative (72% of the drug-related material in urine). In feces, only parent compound was detected, but it is likely that a good proportion of the raltegravir detected in feces is derived from hydrolysis of the glucuronide derivative secreted in bile as observed in preclinical species (Kassahun et al, 2007).…”
Section: Integrase Inhibitors (Inis)mentioning
confidence: 99%
“…In vivo and in vitro studies using isoform selective chemical inhibitors and cDNA-expressed UGTs showed that UGT1A1 is the primary enzyme responsible for the formation of raltegravir-glucuronide (87) (Merck & Co, 2007;Kassahun et al, 2007). In vitro studies demonstrate that raltegravir is not a substrate for cytochrome P450 (CYP) enzymes and does not inhibit CYP1A2, 2B6, 2C8, 2C9, 2C19, 2D6, or 3A or induce 3A4 (Iwamoto et al, 2008).…”
Section: Integrase Inhibitors (Inis)mentioning
confidence: 99%
See 1 more Smart Citation